Effects of Physical Education Learning Activities Using Kohlberg’s Theory of Moral Development and Case Study on Sportsmanship and Learning Achievement of Upper Secondary School Students - Jubram, Chayut; Tingsabhat, Suthana; Phongchini, Wachirawit (Al-HIKMAH Journal, 2024)
The purposes of this research were to evaluate and compare the effects of physical education learning activities based on Kohlberg’s theory of moral development combined with a case study on sportsmanship on the learning achievement of upper secondary school students. The participants included 60 students divided equally into two groups: an experimental group and a control group. The experiment was conducted over a period of 8 weeks for 1 day per week at 60 minutes per day. The tests were conducted to measure sportsmanship along with learning achievement. The data were analyzed using mean, standard deviation, and t-test. The research findings were as follows: 1) the mean scores on the test of sportsmanship and learning achievement of the experimental group were significantly higher after completing the lessons than before at the .05 level of significance. 2) the mean scores on the of test of sportsmanship and learning achievement of the experimental group were significantly higher than the control group at .05 level of significance.